KINERJA PEGAWAI DALAM MENINGKATKAN KUALITAS KERJA PADA DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KABUPATEN MALINAU - Febby Christiani (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this study is to describe and analyze the Employee Performance in Enhancing the Quality of Work. Specified research focus include: The ability of employees to complete the work, discipline employees in providing public services, skills and expertise of personnel in providing quality service jobs generated employees, employee motivation and ethos in providing services to the public, and timeliness in Service. From the results it can be concluded that the performance of the apparatus in the public service in the Department of Communication and Information Technology of Malinau Regency although not yet demonstrated optimal performance but employee performance achieved pretty good indication.